Hiring for sales success: the emerging importance of salesperson analytical skills - Peesker, Karen M.; Kerr, Peter D.; Bolander, Willy; Ryals, Lynette J.; Lister, Jonathan A.; Dover, Howard F. (Elsevier, 2022)
Several studies suggest that accelerating technology, increasing product complexity, and an expanding volume of information in the marketplace are changing sales roles, necessitating a review of the current sales skills required for success. Using mixed methods, we examine the skills required of contemporary B2B salespeople. First, we draw on unique data from 3.8 million LinkedIn job postings to examine which skills sales recruiters are seeking in new hires. Whilst confirming the importance of previously researched sales skills, this identified a sales skill largely disregarded by the extant literature: salesperson analytical skills. We triangulated these findings through interviews with 20 sales executives and developed a scale to measure this new analytical skills construct. Then, to test the scale's predictive and nomological validity, we used survey data from 251 business-to-business salespeople. Results reveal that salesperson analytical skills have both a direct and a moderating effect on sales performance across varying selling situations.
Keywords: Analytical skills; Mixed methods; Sales skills; Salesperson performance; Scale development